Hygiene practices in everyday Life: Exploring the adoption and environmental implications of disposable gloves - Hegnes, Atle Wehn; Heidenstrøm, Nina; Laitala, Kirsi (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
The COVID-19 pandemic has led to increased use of disposable products, notably face masks and disposable gloves. While these items serve as a protective barriers against health hazards, they also pose significant environmental risks due to their resource-intensive production and waste generation. This study explores the adoption of disposable gloves beyond healthcare, probing their use and significance in the daily lives of Norwegian consumers. Employing social practice theory, the research investigates the underlying reasons and ways Norwegian consumers incorporate disposable gloves into various practices, and how more sustainable alternatives could be promoted. The methods encompass mobile ethnography and focus groups with Norwegian consumers. The findings demonstrate that disposable gloves are used to reduce health risk and enhance hygiene in daily life conveniently, consequently increasing waste. Alternative methods for increasing hygiene, such as reusable and longer lasting products or hand washing, are perceived as less hygienic and less convenient. Conclusively, the study sheds light on the complexities of changing material-practice entanglements and offers insights for developing more sustainable hand hygiene practices.